Screening of veterinary drug residues in milk from individual farms in Macedonia - Elizabeta Dimitrieska-Stojkovikj; Zehra Hajrulai-Musliu; Biljana Stojanovska-Dimzoska; Pavle Sekulovki; Uzunov, Risto (Faculty of Veterinary Medicine-Skopje, Ss. Cyril and Methodius University in Skopje, North Macedonia, 2011)
A total of 497 raw milk samples collected at individual farms and collection tanks for milk from eight regions from Macedonia were examined for chloramphenicol, sulfonamides, quinolones and tetracyclines from October 2008 until April 2011. Immunoassay methods were used for the determination of chloramphenicol, sulfonamides and quinolones, and high performance liquid chromatography with Diode Array detection was applied for screening of tetracyclines. The methods were validated according to the recommendations laid down by European Commission Decision 2002/657/EC. The obtained data confirmed that the methods were appropriate for detection of antibiotics determined, at the concentration level of interest. Measured range of concentrations (in μg/kg) was 13.5-147.9 for sulfonamides, 0.6-22.0 for quinolones and 17.4-149.1 for tetracyclines, with calculated mean values (in μg/kg) 24.7 for sulfonamides, 12.6 for qinolones and 41.9 for tetracyclines. None of the analyzed samples showed presence of chloramphenicol over the minimum required performance level value of the screening method. The calculated estimated daily intakes for the average daily consumption of 200 mL of milk for an adult in Macedonia, for the examined antimicrobials, obtained levels 2 to 100 times lower than the values of the acceptable daily intakes fixed by World Health Organization. This indicates that toxicological risk associated with the consumption of analyzed milk could not be considered as a public health issue with regards to these veterinary drugs.
Keywords: milk, veterinary drug residues, chlorampenicol, tetracyclines, sulfonamides quinolones, ELISA, HPLC-DAD, estimated daily intake